2019
DOI: 10.1159/000504445
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Testosterone Deprivation Sensitizes the Middle-Aged Rat Brain to Damaging Effects of Testosterone Replacement

Abstract: Introduction: An increasing number of middle-aged men are being screened for low testosterone levels and the number of prescriptions for various forms of testosterone replacement therapy (TRT) has increased dramatically over the last 10 years. However, the safety of TRT has come into question with some studies suggesting increased morbidity and mortality. Objective: Because the benefits of estrogen replacement in postmenopausal women and ovariectomized rodents are lost if there is an extended delay between est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 95 publications
(137 reference statements)
1
5
0
Order By: Relevance
“…Surprisingly, androgens' effects in animal models of VCID, such as the chronic cerebral hypoperfusion models (e.g., unilateral carotid artery occlusion or bilateral carotid artery stenosis) have yet to be assessed. However, in a rat model of post-stroke dementia, it was found that T replacement after castration increased cognitive deficits following stroke in middle-aged males [122]. It is unclear if the cognitive effect observed was dependent on infarct volume or was independent of stroke severity.…”
Section: Vascular Contributions To Cognitive Impairment and Dementia mentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, androgens' effects in animal models of VCID, such as the chronic cerebral hypoperfusion models (e.g., unilateral carotid artery occlusion or bilateral carotid artery stenosis) have yet to be assessed. However, in a rat model of post-stroke dementia, it was found that T replacement after castration increased cognitive deficits following stroke in middle-aged males [122]. It is unclear if the cognitive effect observed was dependent on infarct volume or was independent of stroke severity.…”
Section: Vascular Contributions To Cognitive Impairment and Dementia mentioning
confidence: 99%
“…However, this effect was found to be mediated by increased oxidative stress, as it could be inhibited by a free-radical scavenger. In contrast to the detrimental effects of T in the context of stroke, in sham animals, T actually improved cognitive performance [122]. Therefore, future studies are needed to determine the role of androgens in models of cerebral small vessel disease and chronic cerebral hypoperfusion.…”
Section: Vascular Contributions To Cognitive Impairment and Dementia mentioning
confidence: 99%
“…With the finer timescale tracking every 2 months in this study, from young adult to middle-aged rats, the impairment in spatial learning and memory could be detected as early as 8 months old (SH-M4) or at the early middle age. This finding partially aligned with the previous studies showing that the deficit in spatial learning and memory on MWM task emerged at the middle age, approximately 12-14 months old (Bizon et al, 2009;Francia et al, 2006;Frick et al, 1995;Frye et al, 2010;Guidi et al, 2014;Smith et al, 2020;Wang et al, 2020). In parallel with the increasing in age and the impairment in spatial learning and memory, male rats had a gradual and marginal decline in serum testosterone levels starting from 8 months old and a significant reduction was detected at 12 months old (or middle age).…”
Section: Discussionsupporting
confidence: 90%
“…Male animals were induced an androgen deficient condition by castration and their cognitive function, i.e., performances on spatial reference version of learning and memory, was assessed by MWM task (Fang et al, 2017;Frye et al, 2010;Jia et al, 2013;Kang et al, 2014;Moghadami et al, 2016;Pintana et al, 2015;Pintana et al, 2016). However, the results were still inconsistent (Benice and Raber, 2009;Hodosy et al, 2012;Pintana et al, 2016;Sandstrom et al, 2006;Smith et al, 2020;Spritzer et al, 2008;Zhao et al, 2018). The discrepancy between studies might be because of the difference in age of animals recruited into the studies, the ages of animals when they were initiated the castration, and duration of time that the animals were held in androgen deficient condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation